THE ROLE OF DIFFERENTIATION OF GOODS AND ITS IMPACT ON THE EFFECTIVENESS OF THE MARKETING STRATEGY OF THE ENTERPRISE - ANHELKO, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article highlights the role of differentiation of goods in ensuring the efficiency of the enterprise marketing strategy. Based on the generalization of approaches to disclosing the content of differentiation of goods, it is stated that it is one of the key tools for improving the efficiency of the marketing strategy of the enterprise, which allows you to stand out among competitors, to form a unique proposal and to create stable consumer loyalty. Attention is emphasized on the classification of differentiation of goods and the characteristics of its main types. It is noted that the choice of a specific type of differentiation or their combination depends on the strategic goals of the enterprise, the expectations of the target audience and the features of the market environment. The key aspects of the impact of differentiation of goods on the effectiveness of the marketing strategy of the enterprise are identified and characterized. Particular attention is paid to the impact of differentiation on the effectiveness of marketing communications. It is shown that products with distinct unique properties, such as convenience, environmental friendliness, personalization or stylish design, are much easier to position in the market. It is emphasized that such characteristics are the basis of effective advertising campaigns and contribute to increased brand interaction with the target audience. The results of the study identify key factors for the success of differentiation strategy, including innovation, product quality, brand recognition and the ability of the enterprise to adapt to changes in consumer preferences. It is concluded that the use of differentiation is an important element of a long-term competitive strategy that provides the enterprise with stable positions in the market and contributes to its further development.